Educational Dimension of Woman's Character in the Narration's of Prophets as Stated in the Holy Qur'an - Al-Omari, Asma' A. M. (2003)
The Holy Qur'an has addressed the needs of women and their status in a way never done before in any other religious text. Woman's exalted position in Islam is due, primarily, to her role as a child rearer. It is she who is considered the "first madrasah" (first school) by Islam, and it is from her that children will learn about their responsibility as future 'standard bearers' of Islam and society. The research examines stories and biographies of women in the Qur'an, narrated by various prophets (peace be upon them) through the ages. These stories have been drawn from sound Islamic sources. not the doubtful narrations of Israelite scriptures, showing, through their life stories, women's attitude nature, some positive and others negative. This provides an authentic and comprehensive view of Muslim women from the Qur'anic perspective. It puts forward an educational model for women to realize their true role in the challenging times in which we live. By studying the attitudes and dispositions of women in the Holy Qur'an and the Sunna of the Prophet Muhammad (peace and blessings be upon him) the research illustrates the merits. morals and role of women as educators in the family, as well as society. It also shows the extent to which a Muslim women can harm or benefit each member of her family. The study also shows the scope of educational techniques in the Holy Qur'an and their impact on the attitudes and character of women. It delineates the educational role of women and the features of women's character through investigation of previous religions and comparison with those in Islam. In this way, we can become more acquainted with the characteristics of women, her tasks, rights, duties and the type of work suited to her outside the family.